Serum kisspeptin levels mainly depend on ovarian expression of Kiss1 mRNA in female rats - Kwon, Ahreum; Eom, Ji Young; Lee, Woo Jung; Choi, Han Saem; Song, Kyungchul; Suh, Junghwan; Chae, Hyun Wook; Kim, Ho-Seong (Frontiers in Physiology, 2022)
The hypothalamic kisspeptin/KISS1 receptor system is essential for puberty onset and reproductive development. Although serum kisspeptin might be associated with puberty, its levels, according to developmental stage, and its origin still remain unclear. This study evaluated the changes in serum kisspeptin levels during puberty and the corresponding Kiss1 mRNA and protein expression in various organs of female rats to identify the source of serum kisspeptin. Tissues from several organs, including the ovaries and anteroventral periventricular nucleus (AVPV) and arcuate nucleus (ARC) in the hypothalamus, were obtained for assessing Kiss1 mRNA and protein expressions. Serum kisspeptin levels progressively increased with developmental stages until the peripubertal stage. The ovaries showed the highest Kiss1 expression among the organs examined. Next, we explored the changes in serum kisspeptin levels and hypothalamic Kiss1 expression in ovariectomized and estradiol-treated ovariectomized rats. Serum kisspeptin levels decreased regardless of estradiol treatment; Kiss1 expression was enhanced by ovariectomy and estradiol treatment in the ARC, while it was decreased by ovariectomy and enhanced by estradiol in the AVPV, suggesting that serum kisspeptin may be associated with pubertal development and mainly depended on ovarian Kiss1 expression. Thus, serum kisspeptin levels are associated with puberty and may serve as a downstream marker of ovarian reproductive function.